Evaluation Context and Input of National Health Insurance in Ternate City (Indian Journal of Public Health Research & Development, 2020)
Context: Implementation of National Health Insurance (JKN) in several regions in Indonesia experiencesdifferences in terms of expected outcomes. The recruitment of participants in business entities, especiallythe micro, small and medium segments, has also not been reported yet. The general objective of this researchis to know the context and input in the implementation of national health insurance in Ternate City. Theresearch method used is qualitative research. The informants in this study were the head of the Indonesiannational health care insurance, the Head of the Health Service, the Head of Planning and Data, the Headof Health Financing, the Head of the Health Center, the Head of the Unit, the Director of the DharmaIbu Hospital. Health insurance program policies in Ternate City are based on regulations issued by theIndonesian national health care insurance and Ternate Mayor Regulations. Inputs Health resources availableat the health center and hospitals are mostly eligible, although there are still officers working health are notfollowing their educational background. Payment of claims at the hospital is still experiencing delays whilepayments for capitation has proceeded according to the rules. Infrastructure facilities available at the healthcenter and hospitals have fulfilled.
Keywords: Health insurance, context, input, evaluation